PERAN END CHILD PROSTITUTION, CHILD PORNOGRAPHY AND TRAFFICKING OF CHIDREN FOR SEXUAL PURPOSES (ECPAT) DALAM MENGATASI CHILD SEX TOURISM DI INDONESIA - Alena Alenka; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study illustrates the role of ECPAT Indonesia in overcoming child sex tourism in Indonesia. Child Sex Tourism is a fundamental violation of children's human rights in the form of sexual violence committed by adults. There are several causes and impacts caused by Child Sex Tourism in Indonesia. In response to this, the role of international organizations, such as ECPAT, is needed. Some of ECPAT Indonesia's efforts in order to overcome this phenomenon are carried out together with fellow network members, the community, and the government through advocacy, prevention, protection, and cooperation activities. The method used in the researcher is descriptive analytical with a qualitative approach. Also, using the concepts of Prostitution, Sex Toursim, and Child Sex Tourism in explaining sexual activities in the tourism industry. This research also uses Clive Archer's International Organization concept, which is as an independent arena, instrument, and actor. The role of ECPAT Indonesia in overcoming child sex tourism in Indonesia is divided into three categories. First, as an arena, ECPAT Indonesia plays a role as a place for discussion in solving problems and as a bridge of communication between tourism stakeholders. Second, as an instrument, in this case ECPAT Indonesia plays a role as a tool used by the government in carrying out international cooperation. Third, as an independent actor, ECPAT Indonesia is able to become a pioneer in child protection policies from sexual exploitation, especially in tourist areas. Keywords: Child Sex Tourism, Sexual Exploitation of Children, and ECPAT